Elaboração de modelo numérico de fluxo de água subterrânea para uma microbacia de água clara na Reserva Florestal Adolpho Ducke, Manaus - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The groundwater flow behavior is of fundamental importance for the development of the biotic environment and maintenance of life, because the availability of water in a given environment influence the growth and distribution of species. The Amazon forest is one of the most important tropical forests in the world, depending on their size and number of species, however, has na environment sensitive to climate variability and change, of anthropogenic or natural origin. From a stationary numerical model developed for the aquifer was possible to estimate the groundwater flow behavior of current and future water using precipitation data report of the Intergovernmental Panel on Climate Change (IPCC – CMIP5 model) for the years 2035, 2065 and 2100. The results show that the value of the base flow stream studied darcyano determined from the flux at the local groundwater aquifer is 3,6x10-4 m3 / s, almost na order of magnitude smaller than the result obtained by determining the flow of the stream in a period without precipitation, 4,8x10-3m3 / s. For the year 2035 is the value of 4,7x10-3 m3 / s, while 2065 and 2100 values are: 2,7x10-3 m3 / s; and 2,5x10-3 m3 /. This downgrade affects the availability of water for vegetation shallow roots. Changes in water level by 2100 could affect the availability of water for the Reserva Florestal Adolpho Ducke.
Keywords: Modelo numérico de fluxo; Balanço hídrico; Numerical flow model; Water balance; Reserva Florestal Adolpho Ducke - Manaus (AM); CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS